76 HOW BLOGS SUPPORT THE TRANSFER OF KNOWLEDGE INTO PRACTICE IN THE FIELD OF DEMENTIA PALLIATIVE CARE: FACILITATORS AND BARRIERS. (25th October 2022) - Rukundo, A; Fox, S; Guerin, S; Kernohan, G; Drennan, J; O'Connor, N; Timmons, S
Abstract: Background: Blogging can help to maximise the impact of one's work in academia and beyond by making research findings accessible for multiple knowledge users. As part of the knowledge exchange and dissemination activities of the Model for Dementia Palliative Care Project, this study explored stakeholders' views of blogs as a means to translate research findings in the field of Dementia Palliative care. Methods: A web-based survey was developed, piloted, and revised. It was distributed electronically via key dementia and palliative care organisations. Complete responses (N=128) were received from healthcare researchers (n=53), healthcare providers (n=46) and others with an interest in healthcare research (n=29). Data were analysed using descriptive statistics and content analysis Results: The preferred methods of reviewing research findings were scientific papers, websites and news articles. Respondents read healthcare blogs "sometimes" (39.1%), with <19% reading them "often" or "very often". Receiving an email notification might increase the likelihood of reading a new blog post for 83% of respondents. Barriers to engaging with blogs included lack of time, preference for other media, lack of awareness regarding available blogs, and concerns about the credibility and source of information. An appropriate length and the author of the blog were key features that encouraged engagement with a blog. Most respondents (37.7 % 'Yes' and 23.0% 'Maybe') would read Dementia Palliative care blogs by the research team. Conclusion: Despite respondents choosing a scientific paper as their preferred method to consume research findings, many indicated an openness to reading blogs on their area of interest. Creating concise, relevant, and credible blogs, and suitably promoting them, could increase the impact and reach of healthcare research, such as in the emerging field of dementia palliative care, and thus promote translation of research findings into practice.